Upaya Meningkatkan Pemahaman Konsep Perubahan Cuaca dengan Model Pembelajaran Berbasis Lingkungan di Kelas III SDN Bendogerit 2 Kota Blitar - Tanjung Anugrah Widhi (IJoIS: Indonesian Journal of Islamic Studies, 2021)
Abstract. Learning in Class III SDN Bendogerit 2, Sananwetan District, Blitar City, during the corona pandemic is not expected to be a barrier in educating students. In learning Weather Changes, usually in learning at school, teachers can make observations with students. So that students can learn directly to understand the concept of learning. Conditions that currently occur in almost all of the world do not become a barrier for teachers to deliver material. The teacher uses an environment-based learning model, so that students at home can do learning by direct observation with the environment around students. Based on this, qualitative research is needed on students in learning climate change. The type of research used is Classroom Action Research (CAR). Data analysis techniques used are data reduction, data presentation, and drawing conclusions.